High‐spatial‐resolution measurements of iron isotopes in pyrites by secondary ion mass spectrometry using the new Hyperion‐II radio‐frequency plasma source. (3rd December 2020) - Decraene, Marie‐Noëlle; Marin‐Carbonne, Johanna; Bouvier, Anne‐Sophie; Villeneuve, Johan; Bouden, Nordine; Luais, Béatrice; Deloule, Etienne
Abstract : Rationale: Iron isotopic signatures in pyrites are considered as a good proxy for reconstructing paleoenvironmental and local redox conditions. However, the investigation of micro‐pyrites less than 20 μm in size has been limited by the available analytical techniques. The development of a new brighter radio‐frequency plasma ion source (Hyperion‐II source) enhances the spatial resolution by increasing the beam density 10 times compared with the Duoplasmatron source. Methods: Here we present high‐spatial‐resolution measurements of iron isotopes in pyrites using a 3 nA–3 μm primary 16 O − beam on two Cameca IMS 1280‐HR2 ion microprobe instruments equipped with Hyperion sources at CRPG‐IPNT (France) and at SwissSIMS (Switzerland). We tested analytical effects, such as topography and crystal orientation, that could induce analytical biases perceptible through variations of the instrumental mass fractionation (IMF). Results: The δ 56 Fe reproducibility for the Balmat pyrite standard is ±0.25‰ (2 standard deviations) and the typical individual internal error is ±0.10‰ (2 standard errors). The sensitivity on 56 Fe + was 1.2 × 10 7 cps/nA/ppm or better. Tests on Balmat pyrites revealed that neither the crystal orientation nor channeling effects seem to significantly influence the IMF. Different pyrite standards (Balmat and SpainCR) were used to test the accuracy of the measurements. Indium mounts must be carefully prepared with a sample topography less than 2 μm, which was checked using an interferometric microscope. Such a topography is negligible for introducing change in the IMF. This new source increases the spatial resolution while maintaining the high precision of analyses and the overall stability of the measurements compared with the previous Duoplasmatron source. Conclusions: A reliable method was developed for performing accurate and high‐resolution measurements of micrometric pyrites. The investigation of sedimentary micro‐pyrites will improve our understanding of the processes and environmental conditions during pyrite precipitation, including the contribution of primary (microbial activities or abiotic reactions) and secondary (diagenesis and/or hydrothermal fluid circulation) signatures.